Oil–water interfaces drive gold precipitation via microdroplet chemistry in thermal geological systems - Guanghui Yuan; Jixuan Wang; Yingchang Cao; Zihao Jin; Fang Hao; Keyu Liu; Yang Li; Hans-Martin Schulz; Jon Gluyas; Richard N. Zare (Proceedings of the National Academy of Sciences, 2025)
Sedimentary basins host high-grade gold mineralization at intersections of auriferous hydrothermal fluids and hydrocarbons. However, the precise mechanism of native gold formation associated with organic matter remains poorly understood. Here, we investigate gold precipitation at oil–water interfaces through in situ thermal experiments using various combinations of oil and HAuCl 4 -bearing solutions. Our results reveal that gold particles form spontaneously following the extensive generation and evolution of water microdroplets at oil–water interfaces at temperatures of 140 to 400 °C. We propose that electrons (e − ), released from the conversion of hydroxide ions (OH − ) to hydroxyl radicals (·OH) in water microdroplets, together with H atoms (·H) formed through electron transfer involving H 3 O + , and spontaneously generated H 2 O 2 from·OH recombination, drive the reduction of Au 3+ to Au 0 . The atomic gold progressively aggregates into Au 0 clusters and Au nanoparticles (AuNPs), ultimately forming micrometer-scale gold particles and wires. This precipitation process occurs within minutes at temperatures above 350 °C and within hours below 200 °C. The experimentally produced gold particles exhibit textures like those in natural ore deposits. This interfacial microdroplet–induced mechanism provides a unique perspective on native gold formation in hydrocarbon-rich geosystems. Beyond its geological significance, this mechanism offers a potentially simplified approach for gold recovery from electronic waste without the need to introduce complex adsorbents or reducing agents into the waste stream.